Oral pemphigus vulgaris - Sharma, Mohit (Journal of Kathmandu Medical College, 2017)
Pemphigus is a group of potentially life-threatening autoimmune mucocutaneous diseases characterized by epithelial blistering affecting cutaneous and/ or mucosal surfaces. Pemphigus affects 0.1-0.5 patients per 100,000 population per year. Oral lesions of pemphigus are seen in up to 18% of patients at dermatology out-patient clinics, but despite the frequency of oral involvement, and novel therapeutic approaches, there are surprisingly few recent studies of either the oral manifestations of pemphigus or their management, and delays in diagnosis are still common. Most patients are initially misdiagnosed and improperly treated for many months or even years. Dental professionals must be sufficiently familiar with the clinical manifestations of pemphigus vulgaris to ensure early diagnosis and treatment, since this in turn determines the prognosis and course of the disease. Pemphigus has been reviewed in the oral literature in the past decade, but several advances in the understanding of the etiopathogenesis, pemphigus variants, and management warrant an update. Here, we report a case of pemphigus vulgaris that was misdiagnosed in its earliest stage. Oral ulceration may arise from a variety of causes. This case illustrates that, although rare, pemphigus vulgaris may need to be included in differential diagnosis.